Peter’s Kingdom Keys Explain Subsequence - Zarley, Kermit (Journal of pentecostal theology, 2015)
This article proposes a solution to the Dunn Debate. It is that Peter’s temporary role in using the metaphorical ‘keys of the kingdom of heaven’ that Jesus promised him in Mt. 16.19 involved both Peter’s preaching the gospel and Jesus’ initial baptizing with the Holy Spirit. Thus, no subsequence (post-conversion Spirit baptism) presumably occurred with the 3,000 Jewish converts at Pentecost in Acts 2 and certainly with the Gentiles in Acts 10 because Peter was the preacher of the gospel when they believed; but subsequence did occur with the Samaritans in Acts 8 because Philip preached and they believed, but Peter came to them days later, using his kingdom keys. After that, with the exception of the anomaly in Acts 19, Dunn is correct that conversion and Spirit baptism always occur simultaneously.